Confessions of a successful CIO : how the best CIOs tackle their toughest business challenges - Roberts, Dan (Dan D.), 1963- (Wiley, 2014)
"Real case studies show IT executives and practitioners how to be better leaders and make better decisionsThe demands placed upon today's Chief Information Officers (CIO) are greater than ever before. The speed at which the amount of changes and complexities that CIO's have to manage is rapidly increasing, and the majority of CIOs are ill-equipped to handle them. As IT becomes a more integral part of business operations and strategies, CIOs must be proficient at decision-making, which is one of the most crucial aspects of IT leadership. With candid personal reflections from respected CIOs and real case studies, this book forms a practical course on decision-making for IT leaders"--